Post a New Question


posted by .

Is this correct now.

Problem #1
solve by completing the square.


My answer: x=-2 +/- sqrt (5)/(2)

Problem #2

solve by using the quadratic formula

My answer: No solution are defined.

You are not completing the square.

x^2 + 4x =- 3/2 now complete the square..
x^2 + 4x + 4 =- 3/2 + 4
(x+2)^2= ( sqrt (2.5))^2
x+2 = +- sqrt 2.5
to your answer above now.

isn't this the same answer as what i have

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question